Canonical variate analysis of chlorophyll content in plants exposed to different lead concentrations in ambient air conditions = Analiza zmiennych kanonicznych zawartości chlorofilu w roślinach eksponowanych na różne stężenia ołowiu w powietrzu atmosferycznym - Budka, Anna; Kayzer, Dariusz; Zbierska, Janina; Borowiak, Klaudia; Barałkiewicz, Danuta; Hanć, Anetta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the results of biomonitoring of Pb in ambient air. For this purpose Italian ryegrass was used to evaluate Pb level. Additionally chlorophyll forms (a+b, a and b) were measured in leaves. Plants were exposed at 5 sites varying in environmental characteristics in the 2011 growing season. A similar set of plants was conducted in control conditions.
Keywords: ołów; chlorofil; życica wielokwiatowa; analiza zmiennych kanonicznych; lead; chlorophyll; Italian ryegrass; canonical variate analysis